The Riverside Reader - Trimmer, Joseph F. and Hairston, Maxine (Boston Houghton Mifflin Company, 1990)
Presents the rhetorical modes as ways of thinking and discovering purpose. Demonstrates clearly the connection between the reading and writing processes. Includes a significantly expanded section on argument and persuasion.
Keywords: Writing